Propuesta de mejora de acceso y movilidad en las PSA de las unidades de generación de hidrógeno en refinería de Cartagena. (2021)
Given the complexities of access and mobility to attend and maintain the equipment and instrumentation that make up the PSA (Pressure Swing Adsorption) in the hydrogen generation units of the Cartagena refinery, the initiative arises to work on an improvement proposal in favor of the ergonomic conditions of this section of the plant, in order to improve and facilitate the circulation of the people who work there, as well as to ensure the normal operation of this and other production plants that depend on the operation of the generating units hydrogen. The proposal to improve access and mobility also aims to eliminate dangers related to work at height, minimize the attention times of routine activities in the PSA and contribute positively to the economy of the refinery in general, providing timely and effective attention by operations and maintainers, but above all guaranteeing the safe permanence of the people who visit and mobilize in the hydrogen purification section of this important processing plant.